Water-soluble meso-thienyl BODIPY therapeutics: Synthesis, characterization, exploring photophysicochemical and DNA/BSA binding properties - Karanlik, Ceren Can; Karanlik, Gurkan; Erdogmus, Ali (ELSEVIER SCIENCE SA, 2023)
Recently, there is rising attention in photodynamic therapy (PDT) compared to traditional methods (immuno-therapy, surgery, chemotherapy or radiotherapy) in the treatment of cancer. This method includes the sensitizers which are activated to generate cytotoxic reactive oxygen species (ROS). BODIPYs are known as one of the sensitizers used in PDT applications. Encouraged by these fact in this study, we present the synthesis of novel BODIPY derivatives with meso-thienyl segment, diiodine moieties at 2-,6-positions and distyryl structure at 3-,5 -positions. The characterization of all compounds was performed by using various spectroscopic methods (UV-Vis, FT-IR, Mass, 1H-NMR and 13C-NMR spectroscopy). To assess the potentials of the synthesized com-pounds in PDT applications, fluorescence, singlet oxygen and photodegradation quantum yields were calculated. Singlet oxygen quantum yields are 0.03, 0.84, 0.13, 0.32 and 0.76 for BODIPY compounds 1-5, respectively. Besides the photophysicochemical studies, DNA/BSA binding experiments for water-soluble BODIPY derivative (5) were examined. For water-soluble BODIPY derivative 5, the DNA binding constant (Kb) is 1.75 x 105 and the BSA binding constant (KBSA) is 4.15 x 104.
Keywords: BODIPY; PDT; DNA binding; Singlet oxygen; NONLINEAR-OPTICAL PROPERTIES; PHOTODYNAMIC THERAPY; DNA PHOTOCLEAVAGE; EXCITED-STATE; DYES; DERIVATIVES; COMPLEXES; PHOTOSENSITIZERS; MECHANISM; Chemistry